2010
DOI: 10.1007/s11557-010-0725-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimal carbon source and pH value for sclerotial formation of Polyporus umbellatus under artificial conditions

Abstract: Polyporus umbellatus is one of the precious medicinal fungi, with sclerotia used as a diuretic agent and antidote in China for many years. This has led to the present interest in producing sclerotia of P. umbellatus in the laboratory due to a decreased abundance in natural sources. Here, we investigated the determining factors for sclerotial formation in P. umbellatus. Five carbon sources, namely, maltose, fructose, glucose, sucrose and soluble starch with different initial pH values were evaluated for their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…The maltose medium consisted of maltose 20 g L −1 , peptone 4 g L −1 , K 2 HPO 4 ∙3H 2 O 1 g L −1 , KH 2 PO 4 0.5 g L −1 , MgSO 4 ∙7H 2 O 0.5 g L −1 , vitamin B1 0.05 g L −1 and agar 12 g L −1 , as described in a previous study14. The sucrose medium contained 20 g L −1 of sucrose; all other components were the same as in the maltose medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maltose medium consisted of maltose 20 g L −1 , peptone 4 g L −1 , K 2 HPO 4 ∙3H 2 O 1 g L −1 , KH 2 PO 4 0.5 g L −1 , MgSO 4 ∙7H 2 O 0.5 g L −1 , vitamin B1 0.05 g L −1 and agar 12 g L −1 , as described in a previous study14. The sucrose medium contained 20 g L −1 of sucrose; all other components were the same as in the maltose medium.…”
Section: Methodsmentioning
confidence: 99%
“…It has been used as an antidote in traditional Chinese medicine for many years, and its fruit body is edible and delicious. It has been reported that maltose and fructose are suitable carbon sources to induce P. umbellatus sclerotia directly from hyphae to sclerotia under artificial conditions121314. Three distinct stages, including sclerotial intiation (SI), development (SD) and maturation (SM), occurred during P. umbellatus sclerotial differentiation1415.…”
mentioning
confidence: 99%
“…Even the P. umbellatus sclerotia can be produced using artificial infection with Armillaria species, asexual propa- gation is still the main pathway adopted on Chinese farms owing to the absence of natural sclerotia (as "seeds") and low production of artificial P. umbellatus sclerotia. 5) It is inevitable to lose genetic diversity during the asexual propagation of P. umbellatus sclerotial production in nature. The extensive gene flow obtained through sexual hybridization between different types could be best implications for the genetic diversity conservation in P. umbellatus, owing to the unavoidable loss of genetic diversity during the long-term asexual propagation.…”
Section: Discussionmentioning
confidence: 99%
“…4) It has been demonstrated that P. umbellatus sclerotia has significant pharmacological effects on treating edema, acute nephritis and diarrhea. 5) Many medical prescriptions containing P. umbellatus, such as Wulingsan (WLS), Choreito, CGX, Khz, Saireito and Yinchenwuling San, have been used to treat various kidney diseases in China, Japan, India and other countries. 6) In addition, P. umbellatus has been verified with various pharmacological activities such as anti-tumor activity, diuretic activity and treatment of chronic kidney disease.…”
mentioning
confidence: 99%
“…In China, P. umbellatus is widely distributed in most provinces (Xing et al, 2012). However, with the rapid decline of the wild resources, cultivars have become predominant (Xing et al, 2011). Information about the genic structure of P. umbellatus and knowledge of the biogeographic structure of it germplasm are lacking for its cultivars.…”
Section: Introductionmentioning
confidence: 99%